Inhibition of p38 MAPK activity promotes ex vivo expansion of human cord blood hematopoietic stem cells - Zou, Jing (2012)
Ex vivo expansion of hematopoietic stem cells (HSCs) depends on HSC self-renewing proliferation and functional maintenance, which can be negatively affected by HSC differentiation, apoptosis, and senescence. Therefore, inhibition of HSC senescence may promote HSC expansion. To test this hypothesis, we examined the effect of inhibition of p38 mitogen-activated protein kinase (p38) on the expansion of human umbilical cord blood (hUCB) CD133(+) cells because activation of p38 has been implicated in the induction of HSC senescence under various physiological and pathological conditions. Our results showed that ex vivo expansion of hUCB CD133(+) cells activated p38, which was abrogated by the p38 specific inhibitor SB203580 (SB). Inhibition of p38 activity with SB promoted the expansion of CD133(+) cells and CD133(+)CD38(−) cells. In addition, hUCB CD133(+) cells expanded in the presence of SB for 7 days showed about threefold increase in the clonogenic function of HSCs and engraftment in non-obese diabetic/severe combined immunodeficient mice after transplantation compared to the input cells. In contrast, the cells expanded without SB exhibited a significant reduction in these HSC functions. The enhancement of ex vivo expansion of hUCB HSCs is primarily attributable to SB-mediated inhibition of HSC senescence. In addition, inhibition of HSC apoptosis and upregulation of CXCR4 may also contribute to the enhancement. However, p38 inhibition had no significant effect on HSC differentiation and proliferation. These findings suggest that inhibition of p38 activation may represent a novel strategy to promote ex vivo expansion of hUCB HSCs.